Two study guides on Lenin's writings : class forces and strategy in the Russian Revolution (1902-1917) ; Soviet power and the Communist International (1918-1919) - Clark, Steve; Riddell, John (New York : Pathfinder, 1988)
Bibliotheek François Vercammen
Engels
Brochure